Intermolecular benzoyl group transfer reactivity in crystals of racemic 2,6-di-O-benzoyl-myo-inositol 1,3,5-orthobenzoate: controlling reactivity by solvate (pseudopolymorph) formation - Krishnaswamy, Shobhana; Shashidhar, Mysore S.; Bhadbhade, Mohan M. (Crystengcomm, 2011)
Racemic 2,6-di-O-benzoyl-myo-inositol 1,3,5-orthobenzoate (rac-3), which usually crystallizes in a monoclinic lattice (Form I, P2(1)/c) from common organic solvents, when crystallized from 2-propanol yielded concomitantly, thin whisker like crystals (Form II, triclinic, P (1) over bar) with inclusion of 2-propanol and water molecules, along with the Form I crystals. Thin fibre-like crystals were also obtained on crystallization from toluene, with inclusion of toluene and water in the crystal lattice (Form III). The Form II and Form III crystals could be converted into the Form I crystals thermally via melt crystallization. Form I crystals exhibit a facile transesterification reaction, but the solvated crystals are unreactive under the same conditions until their transformation to the reactive form. The reactivity patterns of the Form I and Form II crystals correlate well with the molecular organization in them. Since reactivity of the crystals of rac-3 depends on the solvent and the method of crystallization, and the thermal transition of one crystal form to the other, these phase changes can be used as a switch to control the benzoyl transfer reactivity of the constituent molecules in crystals.